Defining “Giant” Mediastinal Tumors: Proposal of a New Clinical–Radiological Classification and Case Report - Emanuel Palade; George Bucur Delaca; Ioana-Medeea Titu; Sergiu Adrian Ciulic; Gabriel Cismaru; Adrian Stef; Simona Manole (Diagnostics)
Background/Objectives: Mediastinal tumors, regardless of their location, can grow to significant sizes, causing compression-related symptoms. The term “giant” mediastinal tumor is inconsistently defined in the literature. This study presents a new clinical–radiological classification (CRC) for mediastinal tumors and evaluates its applicability through a systematic review and a detailed case analysis of a giant thymolipoma. Methods: A systematic review of the literature from the past decade was conducted using PubMed to identify relevant studies on “giant” mediastinal tumors. The inclusion criteria focused on studies involving adult patients with documented tumor size and symptomatology. The review identified 22 studies, with most anterior mediastinal tumors classified as CRC 3 (81%), indicating “giant” tumors. Thymolipomas accounted for 58% of these cases. Tumor volume and weight correlated with symptom severity, guiding surgical approaches. The proposed CRC effectively standardized the definition of “giant” tumors. The case analysis of a 6.84 kg thymolipoma highlighted the challenges of surgical resection, confirming the importance of tailored surgical strategies for large tumors. Results: The review of the literature revealed a significant variation in tumor size and weight across the different mediastinal compartments. Symptomatic tumors (CRC stage 3) located in the anterior mediastinum exhibited the largest volumes and weights, with an average volume of 4949 mL (range: 2013–8840 mL) and an average weight of 4137 g (range: 1575–7500 g). In comparison, tumors in the posterior mediastinum ranked second in terms of size, with an average volume of 2128 mL (range: 1040–5460 mL) and an average weight of 2489 g (range: 1009–6000 g). Tumors located in the middle mediastinum were considerably smaller, with an average volume of 536 mL (range: 21–1092 mL). Among the largest symptomatic tumors in the anterior mediastinum, thymolipomas were the most frequently observed histologic type. These findings underscore a clear size gradient across the mediastinal compartments, with the anterior mediastinum harboring the largest symptomatic tumors, followed by the posterior mediastinum, and the smallest tumors in the middle mediastinum. Conclusions: The novelty of the study lies mainly in the new clinical–radiological classification (CRC) of mediastinal tumors. This classification integrates clinical presentation and cross-sectional imaging findings, offering a standardized framework for tumor reporting. In addition, it provides a precise definition of “giant” mediastinal tumors. The findings emphasize the need for early surgical intervention to prevent severe symptoms and complications. This study also showcases the largest enbloc-resected thymolipoma reported in the recent literature, supporting the utility of the proposed classification in clinical practice.